CHOLINE CHLORIDE BASED DEEP EUTECTIC SOLVENTS: PHYSICOCHEMICAL PROPERTIES AND SPECTROSCOPIC INSIGHTS - Indah Puspita Sari; Annisaa Siti Zulaicha; Sinta Bella Triyanti (Analit : Analytical and Environmental Chemistry, 2024)
This study focuses on the synthesis and characterization of Choline Chloride-based Deep Eutectic Solvents (DES) using Citric Acid (ChCl+CA) and Malic Acid (ChCl+MA) as hydrogen bond donors. The DES were prepared at various molar ratios, and their physicochemical properties, including viscosity, density, pH, water content, and molecular interactions, were comprehensively analyzed. The FTIR spectroscopic analysis revealed key shifts in the functional groups, indicating strong hydrogen bonding between the DES components. While ChCl+CA and ChCl+MA successfully formed stable eutectic solvents at a 1:1 molar ratio, synthesis with higher molar ratios (1:2 and 1:3) and ChCl+Ethylene Glycol (ChCl+EG) were unsuccessful, highlighting the importance of component compatibility and molar ratios. The density and viscosity measurements showed the potential applicability of these DES in extraction processes. This research contributes to the development of DES as green solvents, with future applications in pigment extraction for cosmetic purposes.   Keywords: Deep Eutectic Solvents, Choline Chloride, Citric Acid, Malic Acid, Pigment Extraction, Cosmetic Applications